1997
DOI: 10.1111/j.1600-0714.1997.tb01235.x
|View full text |Cite
|
Sign up to set email alerts
|

Features of odontogenesis and expression of cytokeratins and tenascin–C in three cases of extraosseous and intraosseous calcifying odontogenic cyst

Abstract: To characterize further the nature of calcifying odontogenic cyst (COC), we studied histologically and immunohistochemically an extraosseous and two intraosseous lesions. The extraosseous COC was in continuity with the stratified squamous epithelium of the alveolar mucosa. Immunostaining with monoclonal antibodies showed reactivity of both low- and high-molecular-weight cytokeratins, the degree of coexpression decreasing with the increasing morphological diversity of the cyst/tumour epithelium. Staining for th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
10
0
1

Year Published

2002
2002
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 39 publications
2
10
0
1
Order By: Relevance
“…Another interesting finding was the intra‐epithelial tenascin expression observed in the epithelium of both SOKC and NSOKC. This finding was also encountered by Lukinmaa et al (1997) who found intra‐epithelial tenascin immunostaining in calcifying odontogenic cyst. Based on this, it can be speculated that tenascin has a role on the epithelial cavitation process of OKC, but this possibility has to be investigated in future researches.…”
Section: Discussionsupporting
confidence: 69%
See 2 more Smart Citations
“…Another interesting finding was the intra‐epithelial tenascin expression observed in the epithelium of both SOKC and NSOKC. This finding was also encountered by Lukinmaa et al (1997) who found intra‐epithelial tenascin immunostaining in calcifying odontogenic cyst. Based on this, it can be speculated that tenascin has a role on the epithelial cavitation process of OKC, but this possibility has to be investigated in future researches.…”
Section: Discussionsupporting
confidence: 69%
“…The role of matrix proteins in the development and progression of SOKC and NSOKC have not yet been demonstrated. To date, data on the ECM immunoexpression in odontogenic cysts are scarce, and there are only few previous attempts in this regard (Teronen et al , 1995; Lukinmaa et al , 1997; Hirshberg et al , 1999; Silva et al , 2002; Wahlgren et al , 2003).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The epithelial lining of COC sometimes has the capacity to induce the formation of dental tissue in the connective tissue wall, mainly in the form of odontomas (Shamaskin et al 1989, Buchner 1991, Buchner et al 1990, 1991). Indeed, COC can be found in association with odontogenic tumors such as odontoameloblastoma, adenomatoid odontogenic tumor, calcifying epithelial odontogenic tumor, and ameloblastoma (Lukinmaa et al 1997, Toida et al 1990, Buchner 1991, Buchner et al 1991, Shamaskin et al 1989, Takeda et al 1990). The ghost cells forming the suprabasal layers are large and lightly eosinophilic, with a cytoplasm containing diffuse tonofilaments, but not ortho‐ or parakeratin, and showing a faint outline of the cellular and nuclear membrane (Cawson et al 1998, Van der Waal 1991).…”
Section: Discussionmentioning
confidence: 99%
“…Calcifying odontogenic cyst (COC) is a cystic lesion in which the epithelial lining shows a well‐defined basal layer, an overlying layer resembling stellate reticulum, and masses of “ghost” epithelial cells located in the epithelial cyst lining or in the fibrous capsule (Kramer et al 1992). COC represents about 1% of jaw cysts (Lukinmaa et al 1997, Toida et al 1990), and most cases are located anterior to the 1st permanent molars (Odell & Morgan 1998). Central COC (CCOC) is found most commonly in the 2nd decade of life (more than 40% of cases) (Cawson et al 1998, Buchner 1991, Buchner et al 1990, 1991), while peripheral COC (PCOC) affects individuals most commonly in the 6th decade (Odell & Morgan 1998, Shamaskin et al 1989).…”
mentioning
confidence: 99%